Loss of Mfn1 but not Mfn2 enhances adipogenesis. - Jake P Mann; Luis Carlos Tábara; Satish Patel; Pushpa Pushpa; Anna Alvarez-Guaita; Liang Dong; Afreen Haider; Koini Lim; Panna Tandon; Fabio Scurria; James E N Minchin; Stephen O'Rahilly S; et al. (PLoS ONE)
Objective A biallelic missense mutation in mitofusin 2 (MFN2) causes multiple symmetric lipomatosis and partial lipodystrophy, implicating disruption of mitochondrial fusion or interaction with other organelles in adipocyte differentiation, growth and/or survival. In this study, we aimed to document the impact of loss of mitofusin 1 (Mfn1) or 2 (Mfn2) on adipogenesis in cultured cells. Methods We characterised adipocyte differentiation of wildtype (WT), Mfn1-/- and Mfn2-/- mouse embryonic fibroblasts (MEFs) and 3T3-L1 preadipocytes in which Mfn1 or 2 levels were reduced using siRNA. Results Mfn1-/- MEFs displayed striking fragmentation of the mitochondrial network, with surprisingly enhanced propensity to differentiate into adipocytes, as assessed by lipid accumulation, expression of adipocyte markers (Plin1, Fabp4, Glut4, Adipoq), and insulin-stimulated glucose uptake. RNA sequencing revealed a corresponding pro-adipogenic transcriptional profile including Pparg upregulation. Mfn2-/- MEFs also had a disrupted mitochondrial morphology, but in contrast to Mfn1-/- MEFs they showed reduced expression of adipocyte markers. Mfn1 and Mfn2 siRNA mediated knockdown studies in 3T3-L1 adipocytes generally replicated these findings. Conclusions Loss of Mfn1 but not Mfn2 in cultured pre-adipocyte models is pro-adipogenic. This suggests distinct, non-redundant roles for the two mitofusin orthologues in adipocyte differentiation.